Accuracy of a New Patch Pump Based on a Microelectromechanical System (MEMS) Compared to Other Commercially Available Insulin Pumps: Results of the First In Vitro and In Vivo Studies - Borot, Sophie (J Diabetes Sci Technol, 2014)
The JewelPUMP™ (JP) is a new patch pump based on a microelectromechanical system that operates without any plunger. The study aimed to evaluate the infusion accuracy of the JP in vitro and in vivo. For the in vitro studies, commercially available pumps meeting the ISO standard were compared to the JP: the MiniMed® Paradigm® 712 (MP), Accu-Chek® Combo (AC), OmniPod® (OP), Animas® Vibe™ (AN). Pump accuracy was measured over 24 hours using a continuous microweighing method, at 0.1 and 1 IU/h basal rates. The occlusion alarm threshold was measured after a catheter occlusion. The JP, filled with physiological serum, was then tested in 13 patients with type 1 diabetes simultaneously with their own pump for 2 days. The weight difference was used to calculate the infused insulin volume. The JP showed reduced absolute median error rate in vitro over a 15-minute observation window compared to other pumps (1 IU/h): ±1.02% (JP) vs ±1.60% (AN), ±1.66% (AC), ±2.22% (MP), and ±4.63% (OP), P < .0001. But there was no difference over 24 hours. At 0.5 IU/h, the JP was able to detect an occlusion earlier than other pumps: 21 (19; 25) minutes vs 90 (85; 95), 58 (42; 74), and 143 (132; 218) minutes (AN, AC, MP), P < .05 vs AN and MP. In patients, the 24-hour flow error was not significantly different between the JP and usual pumps (–2.2 ± 5.6% vs –0.37 ± 4.0%, P = .25). The JP was found to be easier to wear than conventional pumps. The JP is more precise over a short time period, more sensitive to catheter occlusion, well accepted by patients, and consequently, of potential interest for a closed-loop insulin delivery system.